Recovery and Incorporation of expanded polystyrene SolidWaste in Lightweight Concrete - Espinoza-Merchán , María Paula; Torres-Parra, Laura Juliana; Rojas-Arias, Nicolas; Coha-Vesga, Pablo Miguel (Ingeniería, 2020)
Context: The high consumption of parts made from expanded polystyrene (EPS) generates environmental problems when disposed. Due to its low density and the low possibility of being utilized in other applications after its disposal, it is necessary to generate an alternative for the recovery and application of this type of waste. This work aims to generate an alternative in the application of EPS waste, particularly as a coarse aggregate in the manufacturing of lightweight concrete. Method: This study used discarded EPS containers as raw material. The material was cleaned, crushed and subsequently reduced in volume by applying acetone, generating pieces of polystyrene (R-PS) to be applied as a coarse aggregate for the manufacturing of lightweight concrete in different proportions. In addition, the pieces were subjected to a chemical attack process in order to observe their behavior. Results: The results show the degree of volume reduction of the EPS pieces by using different acetone ratios, establishing the best degree of reduction (in volume) of this material. Likewise, chemical attack tests show the behavior of R-PS against different agents in R-PS samples. Meanwhile, the failure tests on different concrete samples determine the best R-PS ratio as coarse aggregate for the manufacturing of lightweight concrete. Conclusions: The data obtained in this study show that the application of acetone on EPSW samples reduces its volume by up to 55 %. Concrete failure tests show that an optimum P-RS addition value, to be used as an aggregate in the manufacturing of lightweight concrete, is 7 %. This improves its resistance to chemical agents and weight reduction without significantly reducing the mechanical properties of concrete.